Clothing Brand Value Enhancement Strategies Based on Carbon Peak and Neutrality Goals (Journal of Fiber Bioengineering and Informatics, 2024)
Under the guidance of the “dual carbon” goal, the country has entered a new development period oflow carbon and green, and brand building and value enhancement have become an important directionof the current market development. As a highly polluting apparel industry, the various apparel brandsunder its industry must also seize the opportunity for development and low-carbon transformation andbecome an important force in promoting carbon peak and carbon neutrality. This can be done byenhancing the low-carbon image of the brand, actively exploring the mode and experience of sustainableproduction and consumption, and vigorously promoting the green transformation of the global fashionindustry. In this paper, we first sorted out. We summarised the related research on low-carbon brandvalue. We explored the problems of apparel brands failing to practice low-carbon development fromthree basic dimensions: product, brand marketing and internal brand management. We then proposedcorresponding solutions and strategies to enhance brand value. The study finds that apparel brands cantry to increase innovation investment to create product and service differentiation, improve the internalmanagement mode to enhance the competitiveness of the low-carbon market, and actively fulfil thebrand’s social responsibility to contribute to the realisation of the national goal of “dual carbon”.
Keywords: “Carbon Peaking and Carbon Neutrality”; Clothing Brands; Brand Value; Low Carbon.